The Effect Of Electronic Word Of Mouth (E-WOM) On Social Media On Visiting Decisions And Its Implications For Visiting Satisfaction (Survey On Sausu Glamping Beach Tourism, Parigi Moutong) - Riany Friska Liestyawati; Ira Nuriya Santi; Muzakir Muzakir; Mohammad Zeylo Auriza (UNIVED Press, 2026)
This study examines the influence of Electronic Word of Mouth (E-WOM) on the decisions and satisfaction of tourists visiting Sausu Glamping, a beach tourism destination in Parigi Moutong, Indonesia. Using quantitative methods and involving 120 respondents, data were analyzed through Structural Equation Modeling (SEM) to test four hypotheses about the direct and indirect effects of E-WOM. The results showed that E-WOM has a significant effect on visiting decisions, and also indirectly affects tourist satisfaction through these decisions. The research instrument has proven to be valid and reliable, and the high R² value indicates that the research model is strong enough. This research confirms that reviews and interactions on social media play an important role in shaping visitor perceptions, decisions and satisfaction. Despite limitations in sample size and data collection methods, this study shows that E-WOM is an effective strategy in enhancing tourism experiences and can serve as a reference for destination managers and marketing activities.